Biological carbon pump efficiency in the Humboldt current system off Peru: temperature, salinity and oxygen - Anja Engel (PANGAEA, 2023)
Temperature, salinity and oxygen are measured using sediment traps. The particle interceptor traps were deployed six times (T1, T2, T3, T4, T6, T7) at different locations off Peru (12.0°S-14.6°S and 77.3°W-78.6°W) during the RV METEOR cruises M136 and M138 at four times in April and two times in June 2017.
In: Engel, Anja; Cisternas-Novoa, Carolina; Hauss, Helena; Kiko, Rainer; Le Moigne, Frédéric A C (2023): Biological carbon pump efficiency in the Humboldt current system off Peru: sediment traps during METEOR cruises M136 and M138 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963289